N-POWER (N-BUILT) CRAFTSMEN’S TRAINING PROGRAM AND PERFORMANCE OF BUILDING CONSTRUCTION PROJECTS IN SOUTHWEST NIGERIA - Ijigah, Edoka Augustine; Olubiyi, Kehinde Olugbenga (FUDMA JOURNAL OF SCIENCES, 2025)
In Nigeria, a large number of building construction projects did not meet clients’ satisfaction or are abandoned because of incompetence of craftsmen working on construction sites. This made the Nigerian government to establish (N-Build) programs in 2015 to bridge craftsmen’s training gap. The research study assessed (N-Built) craftsmen’s training program on the performance of building construction projects in South-west Nigeria. Three hundred and ninety-five (395) questionnaires were administered to government agencies, professional bodies, center heads, trainers, and trainees who are stakeholders and are engaged in the (N-Built) craftsmen’s training program. Two hundred and eighty (280) questionnaires was retrieved from the respondent (70.9%). From the result of the study, the major hindrances to the progress of (N-Built) craftsmen’s training are collection of tools during and after the training, engagement on six-month’ internships, collection of feedback from the trainees, and relating the impact of the training on the economy. The major skills needed for (N-Built) craftsmen training is tool handling technique, communication of drawing, practical competence, lateral and horizontal verbal communication, and active listening skills. While the factors affecting craftsmen’s (N-Built) training programs in Southwest Nigeria are the availability of government funding, inconsistency in government policies, inadequate provisions of deliverables, late arrival of materials for the training, and improper planning. The paired sample t-test result of the proposed effect of (N-Built) craftsmen’s training on construction project performance indicated a significant relationship (p-value < 0.05). In conclusion, (N-built) craftsmen’s training should be encouraged to improve the performance of building construction projects in Nigeria.